Characteristics of Nitrate Pollution in Shallow Groundwater on the South Slope of Mount Merapi, Yogyakarta, Indonesia - Adi, Restu Dwi Cahyo; Wilopo, Wahyu; Setiawan, Hendy (Badan Riset dan Inovasi Nasional, 2023)
Groundwater is the primary clean water source for most Indonesian society. The increasing use of groundwater is inevitable due to the rapid development in Indonesia, particularly in Yogyakarta. Shallow aquifers are vulnerable to contamination due to anthropogenic influences. Therefore, this research aims to determine shallow groundwater's physicochemical and chemical characteristics on the southern slope of Mount Merapi, specifically focusing on nitrate and chloride concentrations in groundwater. This research collected monthly data from eighteen dug wells or springs and rainfall data in the study area during the rainy and dry seasons from August 2022 to January 2023. The analyzing sample used argentometry to determine chloride concentration and ultraviolet spectrophotometric to determine nitrate concentration in Yogyakarta Environmental Health and Disease Control Technical Center (BBTKLPP) laboratory. The physicochemical parameters were tested directly in the field using Hanna instruments. The results indicate that a significant portion of shallow groundwater has high nitrate concentrations, corresponding to the growing settlements in the research area. Furthermore, according to the comparison graph between nitrate and chloride, the nitrate source was indicated as anthropogenic. Fecal matter from sanitation practices using septic tanks will likely influence the nitrate increase.